A "synaptoplasmic cistern" mediates rapid inhibition of cochlear hair cells - Lioudyno, Maria (2004)
Cochlear hair cells are inhibited by cholinergic efferent neurons. The acetylcholine (ACh) receptor of the hair cell is a ligand-gated cation channel through which calcium enters to activate potassium channels and hyperpolarize the cell. It has been proposed that calcium-induced calcium release (CICR) from a near-membrane postsynaptic store supplements this process. Here, we demonstrate expression of type I ryanodine receptors in outer hair cells in the apical turn of the rat cochlea. Consistent with this finding, ryanodine and other store-active compounds alter the amplitude of transient currents produced by synaptic release of ACh, as well as the response of the hair cell to exogenous ACh. Like the sarcoplasmic reticulum of muscle, the "synaptoplasmic" cistern of the hair cell efficiently couples synaptic input to CICR.